The Great Failure in the Pandemic. Power-critical comments on the intersectional dimensions of a politically made catastrophe. - Meisterhans, Nadja (Momentum Quarterly, 2022)
COVID-19 is not a natural disaster. From a human rights perspective, COVID-19 is rather an expression of a lack of global solidarity and a glaring political failure – at the national, European, and global level. The central idea of this contribution is that the structural causes and effects of the global health crisis (not only since the pandemic) have been neglected. Accordingly, the fading out of the structural causes of multiple and interconnected crises is one of the main reasons why the pandemic exacerbates intersectional inequalities and power asymmetries on a global scale and why structurally disadvantaged social groups are abandoned by populist governments in an almost necropolitical manner and sometimes even made scapegoats. Despite these skeptical diagnoses, the last part of the article sketches out contours of a critical global governance for health, which could be applied in post-pandemic times.